Effect of Sexual Education on Sexual Function of Iranian Couples During Pregnancy: A Quasi Experimental Study - M Heidari; F Aminshokravi; F Zayeri; SA Azin (JRI, 2018)
Background: The aim of this study was to evaluate the impact of husbands' participation in sexual education on sexual function during pregnancy. Methods: This quasi experimental study was conducted on 123 couples who were divided in two intervention (A: couples, B: pregnant women) and one control (C) groups. Group A couples received sex education, Group B women received sex education without their spouses, and Group C women received routine prenatal care without sex education. Sexual functions of couples were assessed by Female Sexual Function Index (FSFI) and International Index Erectile Function (IIEF) questionnaires, before sex education, four weeks after the intervention, at the end of the second trimester and at the end of the third trimester. Results: Mean total scores of FSFI and IIEF were not different at baseline in three groups. Repeated measure analysis showed significant differences between groups (A and B with C) in the mean total scores of FSFI and IIEF during the third trimester. The mean total scores of the two intervention groups of A and B were not significant. Conclusion: According to the results of the present study, promoting the sexual function of pregnant women needs to include the sex education on prenatal care. Whereas spouses’ participation was suggested to have a great role in the effectiveness and strengthening of the education in various studies, this study showed that the lack of spouses’ participation for whatever reasons may lead to the same results of previous studies which emphasized the necessity of spouses’ participation.